Ryukyu-Northern Malay Archipelago relations from the 14th to the 17th century - Ku, Boon Dar (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2019)
The record of the trading enterprises of the Ryukyuans in the late 14th to the early 17th century constitutes not only an important chapter in the Ryukyuan history, but also a notable part of the history of the Malay Archipelago as a whole. This study will be exploratory in nature as it looks into several key questions. These include the nature of the relationship between Ryukyu and the Northern Malay Archipelago and how their relationship was developed during this particular period. To do this, the paper will first examine and reconstruct the history and historiography of the Ryukyu-Northern Malay Archipelago relations. Secondly, it will explore their maritime network during the rapid cultural development of the Ryukyu Kingdom. This study also hopes to shed new light upon the historical connection of the two regions while at the same time offer some new perspectives on their politics as well as their maritime network and bond.